Disease burden due to PM2.5 pollution before and after air quality improvement in Shijiazhuang - Yue QU; Fangting ZENG; Fengge CHEN; Mingyang GUAN (环境与职业医学, 2024)
BackgroundAir pollution has gradually become a major environmental and public health problem faced by countries around the world. Hazy weather not only affects the health of the population, but also poses a threat to social and public safety. China has successively promulgated policies such as the "Ten Articles on Atmosphere" and the Three-year action plan to fight air pollution, aiming to improve ambient air quality. It is clear that the Beijing-Tianjin-Hebei region has accomplished the set targets and improved air quality according to the environmental monitoring data of 2017. ObjectiveTo assess air quality improvements through the evaluation of the disease burden due to fine particulate matter (PM2.5) pollution in Shijiazhuang City before and after the air quality improvement from 2014 to 2021, including fatalities and health economic losses attributed to PM2.5 pollution. MethodsData on causes of death, PM2.5 concentrations, the number of permanent residents at the end of the year, gross regional product, and disposable income per capita in urban areas of Shijiazhuang were collected from 2014 to 2021. Total, non-accidental, circulatory, and respiratory deaths due to PM2.5 pollution were estimated by global exposure mortality models (GEMM). Health and economic losses due to selected diseases were calculated by value of statistical life (VOSL). ResultsDuring the study period, the average annual concentration of PM2.5 in Shijiazhuang was highest in 2014, and began to decline year by year in 2017, but all exceeded the current national limit of the second level of ambient air quality standards (35 μg·m−3). The total deaths, non-accidental deaths, circulatory disease deaths, and respiratory disease deaths attributed to PM2.5 pollution from 2014 to 2021 were 41326, 40246, 21792, and 5022, respectively; the associated health economic losses were 37.362, 36.369, 19.695, and 4.535 billion yuan, respectively. From the perspective of improved air quality, both the number of attributed deaths and health economic losses had declined in a volatile manner since 2017, with a significant decrease in 2019. If the average annual concentration of PM2.5 reached the second-level limit of China's ambient air quality standard (35 μg·m−3), the total deaths, non-accidental deaths, and deaths from circulatory diseases and respiratory diseases due to PM2.5 pollution would deducted by about 17000, 16000, 9000, and 2000, respectively; the corresponding health and economic losses would decreased by 15.201, 14.761, 7.959, and 1.859 billion yuan, respectively. If the average annual concentration of PM2.5 reached the latest PM2.5 air quality guidelines (5 μg·m−3) proposed by the World Health Organization, the total deaths, non-accidental deaths, circulatory disease deaths, and respiratory disease deaths due to PM2.5 pollution would deducted by 36000, 35000, 19000, and 4000, respectively, and the corresponding health and economic losses would reduced by 32.673, 31.796, 17.211, and 3.969 billion yuan, respectively. ConclusionPM2.5 pollution can lead to severe mortality burden and economic loss. Under the implementation of the State Council's "Ten Articles on Atmosphere" and the Three-year action plan to fight air pollution, Shijiazhuang's PM2.5 concentration and health economic losses have been significantly reduced, and further control of PM2.5 pollution can achieve greater health benefits and economic gains, affirming the positive results of local air pollution prevention work.